Revival of the tailoring industry - A concept. - Loi, Shing Ping. (2008)
This project is a continuation of the effort to study revival strategy for the tailoring. The industry as a traditional line of business has not made many changes over the years. It seems to be diminishing because it has been slow in adjusting itself to the changing world.